Front Cover Picture: Chemoenzymatic Approaches to the Synthesis of the Calcimimetic Agent Cinacalcet Employing Transaminases and Ketoreductases (Adv. Synth. Catal. 11/2018). Issue 11 (17th May 2018) - Marx, Lisa; Ríos‐Lombardía, Nicolás; Farnberger, Judith F.; Kroutil, Wolfgang; Benítez‐Mateos, Ana I.; López‐Gallego, Fernando; Morís, Francisco; González‐Sabín, Javier; Berglund, Per
Abstract : The front cover picture, provided by Javier González‐Sabín, Per Berglund and collaborators, illustrates several chemoenzymatic routes which have been explored for the preparation of the API cinacalcet. Transaminases (TAs) and ketoreductases (KREDs) turned out to be useful biocatalysts for the preparation of key optically active precursors, the enantiopure ( R )‐amine and enantiopure ( S )‐alcohol. The ( S )‐alcohol was converted into the enantiopure amine, which can be alkylated to cinacalcet in one step. In a preparative‐scale synthesis the TA‐based approach was performed in aqueous medium and led to enantiopure cinacalcet in two steps and 50% overall yield. Details can be found in the full paper on pages 2157–2165 (L. Marx, N. Ríos‐Lombardía, J. F. Farnberger, W. Kroutil, A. I. Benítez‐Mateos, F. López‐Gallego, F. Morís, J. González‐Sabín, P. Berglund, Adv. Synth. Catal .2018, 360, 2157–2165; DOI:10.1002/adsc.201701485 ).